EImplantation of a garden medicinal and condiment for use school community - Theisen, Geovane Rafael; Borges, Grazieli Mafalda; Vieira, Marilene Ferrari; Konflanz, Tais Lazzari; Neis, Franciele Antonia; Siqueira, André Boccasius (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
This work is part of an internship in educational spaces. The activity was developed with students from grade 4 to a state school in municipality of Palmeira das Missões/RS under the guidance of three students of Biological Sciences, Federal University of Santa Maria Campus Palmeira of Missões /RS. The educational proposal was developed a garden medicinal and condiment on institution environmental. This proposal aimed to bring together knowledge about the species of therapeutics plants used by the school community. The mode of practice developed served to integrate the students about the importance of plants in day to day, allowing them to contextualize the topic and expand their knowledge on the subject..